Effects of whole-body vibration training as an adjunct to conventional rehabilitation exercise on pain, physical function and disability in knee osteoarthritis: A systematic review and meta-analysis - Yan Peng; Qi Qi; Chai Li Lee; Yan Ling Tay; Siaw Chui Chai; Mohd Azzuan Ahmad (PLoS ONE, 2025)
Background Knee osteoarthritis (KOA) is a prevalent degenerative joint condition that impairs mobility and quality of life. While whole-body vibration training (WBVT) shows promise as an adjunct to conventional KOA rehabilitation, its efficacy remains unclear due to inconsistent clinical evidence. Objective To elucidate the combined effects of WBVT and rehabilitation exercise on pain, physical function, and disability in KOA management through a systematic review and meta-analysis. Methods A comprehensive search was conducted across eight electronic databases (PubMed, Web of Science, Embase, PEDro, SPORTDiscus, Scopus, ScienceDirect, and China National Knowledge Infrastructure) up to February 2024. Inclusion criteria were (i) randomized controlled trials comparing combined WBVT and rehabilitation exercise versus rehabilitation alone in KOA (ii) reported clinical outcomes (iii) human studies, and (iv) publications in English or Chinese. Trial quality was assessed using the PEDro scale and Cochrane risk-of-bias tool. The meta-analysis employed random-effects models in Review Manager 5.3 to account for heterogeneity, supported by sensitivity analyses for robustness and subgroup analyses on WBVT frequency effects. Results Sixteen RCTs comprising 589 participants were included. The systematic review found that WBVT combined with conventional rehabilitation significantly reduced pain and improved physical function in KOA patients. The meta-analysis quantified these effects, showing that WBVT significantly (i) reduced knee pain (MD = −0.43, 95% CI [−0.70, −0.16], p = 0.002), with greater reductions observed from high-frequency WBVT, and (ii) increased isokinetic knee peak torque compared to rehabilitation exercise alone. No significant differences were found in balance, functional mobility, and disability outcomes. Sensitivity analysis of high-quality trials supported these results. However, the heterogeneity among studies and variations in control group interventions warrant cautious interpretation. Conclusion WBVT seems to be effective in reducing pain and enhancing muscle strength in KOA patients when used in conjunction with conventional rehabilitation. Future high-quality RCTs must standardize WBVT protocols, emphasize long-term follow-up, and refine dosage for clinically meaningful outcomes. Systematic review registration: International prospective register of systematic reviews (PROSPERO CRD42024508386)